A multi-image codebook approach for secure text transmission - Omar Fitian Rashid; Saba A. Tuama; Humam Al-Shahwani (PLoS ONE, 2025)
In modern digital communication, Confidentiality of text transmission is remains a concern in the current online communication as cyber threats and intrusion. To address these challenges, this paper proposes a dual-layered security system that integrates cryptography and multi-image steganography to strengthen text protection during transmission. The cryptography layer is done based eight steps; in the first one, the message is converted to ASCII format, then convert the ASCII values into their equivalent binary numbers and make a complement to the binary values where each 0’s becomes 1’s and vice versa. In the next step, it needs to enter a key that includes a combination of characters, numbers, and special characters. This key is also converted to binary, and then the XOR operation is made between the message of the binary values and the key. In the fifth step, switching the values of each two adjacent binary values are together and converted to decimal values. While the second layer embeds the ciphertext in several cover images using a randomized codebook along with the Least Significant Bit (LSB) substitution, thus enhancing undetectability. Experimental evaluation demonstrates fast execution times for both the encryption/decryption processes and the multi-image hiding/extraction procedures. The achieved results validate that the proposed system provides an efficient and highly secure framework for protecting sensitive information.